Customer Satisfaction Analysis In Electronic Governance Services (E-Government): A Case Study Of The Usage Of The Online Service Portal In The Central Bureau Of Statistics Of Diy Province, Yogyakarta - Nasrullah Ahmad Fauzan (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to evaluate the satisfaction level of customers/community with the e-Government services provided by the Central Bureau of Statistics (BPS) of the DIY Province and to explore their experiences in using these services. Through comprehensive analysis, this study provides an overview of the effectiveness and user experiences of e-Government initiatives in the DIY Province. The research adopts a qualitative approach and utilizes three main data collection techniques: interviews, observations, and documentation at the Central Bureau of Statistics (BPS) of DIY Province. Interview data encompasses users' views, opinions, and experiences with e-Government services, analyzed descriptively to understand user satisfaction and experiences with the provided services. BPS Provinsi D.I. Yogyakarta operates through four main stages of statistical activities, ensuring accuracy and completeness of provided statistical data. Users of the online service portal face challenges such as data incompleteness and unfamiliar portal interface, although improvement efforts, including inventory data collection and integration of live chat feature, have been initiated. Additionally, a Customer Satisfaction Survey (CSS) indicates high satisfaction levels, with a 94.06% satisfaction index for service quality and 97.14% satisfaction for facilities provided by BPS Provinsi D.I. Yogyakarta.